2013
DOI: 10.1002/art.37969
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence in Systemic Sclerosis: Meta‐Analysis of Population‐Based Cohort Studies

Abstract: Objective. To examine cancer incidence in patients with systemic sclerosis (SSc) through a meta-analysis of population-based cohort studies.Methods. Five different databases (Medline, Scopus, CINAHL [Cumulative Index to Nursing and Allied Health Literature], Web of Science, and Cochrane Collaboration) were searched for articles published between January 1966 and May 2012; review articles and the reference lists from the articles that resulted from the search were also evaluated. Population-based cohort studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
121
2
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 44 publications
14
121
2
13
Order By: Relevance
“…In many cohort, prospective, retrospective, and case control studies, hematological cancers such as non-Hodgkin lymphoma, leukaemia, multiple myeloma, and myeloproliferative neoplasms were reported in patients with SSc (3-6). A 2.5-fold increased risk for hematological cancers in a nationwide population-based cohort study was reported by Olesen et al (8) Paraneoplastic scleroderma may accompany hematologic malignancies (3,4). An increased risk for non-Hodgkin lymphoma was reported in female patients with SSc (1).…”
Section: Case Presentationmentioning
confidence: 88%
See 1 more Smart Citation
“…In many cohort, prospective, retrospective, and case control studies, hematological cancers such as non-Hodgkin lymphoma, leukaemia, multiple myeloma, and myeloproliferative neoplasms were reported in patients with SSc (3-6). A 2.5-fold increased risk for hematological cancers in a nationwide population-based cohort study was reported by Olesen et al (8) Paraneoplastic scleroderma may accompany hematologic malignancies (3,4). An increased risk for non-Hodgkin lymphoma was reported in female patients with SSc (1).…”
Section: Case Presentationmentioning
confidence: 88%
“…In addition, the risk for hematological cancers has a lower frequency than solid tumors in SSc. (2)(3)(4). The occurence of myelodisplastic syndrome (MDS) secondary to SSc is rarely reported in literature (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Malignancy associated with systemic scleroderma has been described as a direct consequence of fibrosing process involving internal organ as well as an origin of paraneoplastic manifestation predominately linked with lung cancer, liver cancer, urinary tract or malignant hematologic disorders (3,4). Up to date, several studies have pointed at sudden development of morphea before or in brief time interval after the diagnosis of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison with other experiences performed in other countries regarding age-related cancer screening procedures was not feasible on the grounds of the different local guidelines. Recently, two meta-analyses were published about cancer incidence among SSc patients (27,28). The relative risk to develop all invasive cancer was quantified in 1.75 (27).…”
Section: N Discussion and Conclusionmentioning
confidence: 99%
“…The relative risk to develop all invasive cancer was quantified in 1.75 (27). SSc men were more prone than women to develop neoplastic diseases (28). The results for selected cancers showed that SSc patients have in comparison with the general population a higher risk of developing lung and haematological neoplasms (27,28), as well liver and bladder cancers (28).…”
Section: N Discussion and Conclusionmentioning
confidence: 99%